Survival after Partial Breast Brachytherapy in Elderly Patients with Non-Metastatic Breast Cancer - Yao, Nengliang (2013)
BACKGROUND: Despite growing utilization of accelerated partial breast irradiation using brachytherapy (APBI-Brachy) for elderly breast cancer patients, there are limited data from randomized phase III trials to support its routine use. This study uses population-based data to examine whether APBI-Brachy results in comparable survival rates compared to whole breast irradiation (WBI). METHODS: A sample of 29,647 female patients diagnosed with non-metastatic breast cancer in 2002–2007 treated with breast -conserving surgery and radiotherapy was identified in the SEER-Medicare dataset. Log-rank tests, Cox proportional hazards models, instrumental variable analysis, and subgroup analysis were used to study the comparative effectiveness of APBI-Brachy and WBI. RESULTS: During a median follow-up of 3.6 and 4.8 years, 123 (7.7%) and 3438 (13.6%) patients died following APBI-Brachy and WBI, respectively. Recurrence-free survival (p-value=0.9711) and overall survival rates (p-value=0.0551) did not differ significantly between the two radiation modalities. After accounting for tumor characteristics, patient characteristics, community factors, and comorbidities, the recurrence-free survival (HR=1.05; 95% CI, 0.90–1.23; p=0.5125) and overall survival (HR= 0.87; 95% CI, 0.72–1.04; p=0.1332) were still not significantly different between patients treated with APBI-Brachy and WBI. CONCLUSION: Partial breast brachytherapy and WBI resulted in similar recurrence-free and overall survival rates in this cohort of elderly breast cancer patients, even after adjustment for the more favorable characteristics of patients in the former group. These findings will need to be confirmed by the randomized trials comparing these modalities.